Cachexia, dietetic consultation, and survival in patients with pancreatic and periampullary cancer: A multicenter cohort study. (27th October 2020) - Latenstein, Anouk E. J.; Dijksterhuis, Willemieke P. M.; Mackay, Tara M.; Beijer, Sandra; van Eijck, Casper H. J.; de Hingh, Ignace H. J. T.; Molenaar, I. Quintus; van Oijen, Martijn G. H.; van Santvoort, Hjalmar C.; de van der Schueren, Marian A. E.; de Vos‐Geelen, Judith; de Vries, Jeanne H. M.; et al.
Abstract: It is unclear to what extent patients with pancreatic cancer have cachexia and had a dietetic consult for nutritional support. The aim was to assess the prevalence of cachexia, dietitian consultation, and overall survival in these patients. This prospective multicenter cohort study included patients with pancreatic cancer, who participated in the Dutch Pancreatic Cancer Project and completed patient reported outcome measures (2015–2018). Additional data were obtained from the Netherlands Cancer Registry. Cachexia was defined as self‐reported >5% body weight loss, or >2% in patients with a BMI <20 kg/m 2 over the past half year. The Kaplan–Meier method was used to analyze overall survival. In total, 202 patients were included from 18 centers. Cachexia was present in 144 patients (71%) and 81 of those patients (56%) had dietetic consultation. Cachexia was present in 63% of 94 patients who underwent surgery, 77% of 70 patients who received palliative chemotherapy and 82% of 38 patients who had best supportive care. Dietitian consultation was reported in 53%, 52%, and 71%, respectively. Median overall survival did not differ between patients with and without cachexia, but decreased in those with severe weight loss (12 months (IQR 7–20) vs. 16 months (IQR 8–31), p = 0.02), as compared to those with <10% weight loss during the past half year. Two‐thirds of patients with pancreatic cancer present with cachexia of which nearly half had no dietetic consultation. Survival was comparable in patients with and without cachexia, but decreased in patients with more severe weight loss. Abstract : The extent of cachexia and dietetic consultation in patients with pancreatic cancer in the real‐world setting is unclear. This prospective multicenter cohort study found that in patients, diagnosed between 2015 and 2018, two‐third presented with cachexia of whom nearly half had no dietetic consultation. Survival was comparable in patients with and without cachexia, but decreased in patients with more severe weight loss.